The The Effectiveness Of Health Education Training With The Phantom Media Demonstration Method On Knowledge And Awareness Skills - Gading Niken Pramesti (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2024)
Background: Breast cancer is the highest cause of cancer death in women in Indonesia. The delay in treatment was due to a lack of public knowledge about breast cancer and the lack of knowledge on how do breast-examinnation (BSE) for early detection of breast cancer. The demonstration method demonstrates a process that displays examples of behavior so thatit can be known and understood by real targets. Objectives: The purpose of this study was to analyze the effectiveness of health training through demonstration methods with phantom media on BSE knwoledge and skills in female students. Research Metodes: this study used a quantitative research, with a one group pretest-postest design approach. The population in this study was SMA Negeri 3 Samarinda as many as 198 students, then the sample size was 66 students. Taken by simple random sampling. The research instrument was a knowledge and skills questionnaire in the form significance level of ρ value < α 0.05. Results: Statistical results using the wilcoxon test showed that ρ value < α 0.05, which means that there is an effect of health education on female students knowledge and skills about BSE. Conclusion: There is the ifluence of health education about BSE using the phantom media demonstration method in iincreasing the knowledge and skills of SMA Negeri 3. It is hoped that it can be input and informattion for young female students.